The effectiveness of social media in promoting small restaurant from the customer perspectives: Bukit Tinggi 2, Klang / Rossyamila Mat Kassim & Norshahidah Musa - Mat Kassim, Rossyamila; Musa, Norshahidah (Faculty of Hotel and Tourism, Universiti Teknologi MARA, 2017)
The study and usage of social media as an advertising tool is a recent issue that has yet to gain understanding from many people. However, it has been capitalised by many business firms and organizations to- expand business growth. A firm incorporating social media as part of their marketing toots are assumed to be up with the times and have a competitive edge over their competitors, which in turn, leads to a positive impact on their sales and profitability. This research initiative primarily intends to investigate the impact that social media has on the numbers of customers of a restaurant. It shows the role that social media play as a tool for small restaurants and food and beverages entrepreneurs to execute advertising and promotional activities. Hence, the aim and objective of this research is to identify the most widely used social media amongst customers and to investigate the effectiveness of social media as a tool to promote a restaurant. A random survey was conducted with 92 respondents from five participating restaurants outlet. The result of the study shows positive results on the effectiveness of social media being used by small restaurants. Based on the findings, it is highly hoped that this study will further enhance knowledge and awareness about the use of social media in promoting small restaurants from the customers’ perspectives. Theoretical and practical implications, limitations and further directions are also presented in the paper.